Coronary artery stenosis. - Weir, I (2006)
The near exponential rise in percutaneous coronary intervention(PCI) in the treatment of patients with coronary artery disease and the consequent decline in referral of patients for coronary artery bypass grafting (CABG) has lead to a crisis in cardiac surgery. Is CABG, one of the most successful and widely applied surgical procedures, about to follow surgery for peptic ulcer disease into obsolescence? The question has serious implications for service provision and training as well as for informed patient consent. Keith Dawkins puts the case for PCI and gives a very clear and concise account of its inexorable rise to pre-eminence. David Taggart has taken on the Goliath of interventional cardiology and its associated industry by persuasively marshalling the data from the evidence base which strongly favours surgery in triple vessel and left main coronary disease. He points to the lack of long-term results and also to the weaknesses of many of the comparative studies so far published. His arguments have been positively received on both sides of the Atlantic but it is by no means certain that they will bring about the multidisciplinary approach to providing patients with treatment options which he and others advocate. It also remains to be seen whether the evidence base when it is eventually acquired will vindicate the present increasing dominance of PCI over CABG.